Temporal effect of interpretation in CJEU judgments in C-326/15 DNB Banka and C-605/15 Aviva: implications on cost-sharing in Latvian financial and insurance services sectors - Šveha, Juta (Riga Graduate School of Law, 2019)
The main objective of the paper is to analyse the temporal effect of the interpretation of Article 132(1)(f) of the VAT Directive given by CJEU in Latvian case C-326/15 DNB Banka and Polish case C-605/15 Aviva with regard more specifically to Latvian financial and insurance services sector. In doing so, the author aims to determine at which moment Latvian financial institutions and insurance companies are legally obliged to cease the application of the cost-sharing exemption to services provided within the cost-sharing group pursuant to CJEU’s judgments in C-326/15 DNB Banka and C-605/15 Aviva cases.
Keywords: Research Subject Categories::LAW/JURISPRUDENCE::Other law::European law; Insurance; Latvia